Improving Marketing Efficiency and Effectiveness by Optimizing Product Innovation through E-Commerce Mediation - Rini Revina Windiyani; Talitha Zhafirah; Salma Yulia Rahmah; Yusuf Yusuf (Pusat Publikasi Nusantara, 2024)
This study analyzes the relationship between product innovation, E-Commerce, and marketing performance in Cirebon Regency's batik business actors. This study uses a quantitative research design with a Correlational Design to evaluate the relationships between variables. The results show that the majority of respondents in this study were consumers aged between 31-40 years (48%), followed by ages 41-50 years (28%), and ages 20-30 years (15%). However, it can be concluded that product innovation does not have a significant effect on marketing performance. It supports sustainable product purchasing through improved access, recommendation systems, and environmentally friendly packaging. It also helps batik businesses to improve their feasibility, cultivate strategic partnerships and increase their contacts with customers and suppliers. Therefore, it is becoming very important for business owners to improve marketing performance and understand how E-commerce works as a communication tool, marketing and how they can significantly grow their business.